Conductive bacterial cellulose by in situ laccase polymerization of aniline - Shim, Euijin (2019)
Conductive and colored bacterial cellulose (BC) was developed by entrapment of polyaniline (PANi) onto dry BC membranes. The polyaniline was produced by in situ green polymerization of aniline by Myceliophthora thermophila laccase at pH = 4, 25°C, in the presence of a mediator, 1-hydroxybenzotriazol (HBT), using two different reactors, a water bath (WB) and an ultrasonic bath (US). MALDI-TOF and 1H NMR characterization of the experiment solutions confirmed the efficient polymerization of aniline by laccase. The dried BC membranes with entrapped polyaniline showed electrical conductive behavior and strong coloration, opening novel routes for the exploitation of functionalized bacterial cellulose as a green material for technical textiles, wearables, and other applications.